Identification of Mixed-Meal Effects on Insulin Needs and Glycemic Control. Issue 27 (2018) - Reiterer, Florian; Freckmann, Guido; del Re, Luigi
Abstract: Patients with type 1 diabetes mellitus (T1DM) usually determine their bolus insulin requirements using methods from advanced carbohydrate counting (ACC). In standard ACC only the carbohydrate content of the meal is used, whereas newer research suggests that also fat and protein should be considered. Especially meals with a high fat content are reported to require additional insulin. However, it remains disputed how to account for mixed meal composition appropriately when calculating bolus insulin needs. The current paper shows how the previously published Adaptive Bolus Calculator (ABC) method can be used to identify the effect of the mixed meal composition on the bolus insulin requirements. Additionally, a pragmatic strategy is proposed how the mixed meal composition can be taken into account when determining the bolus insulin needs with the ABC method. It is shown in Deviation Analysis simulations that taking into account the mixed meal composition for calculating the bolus insulin needs leads to a small, but statistically significant improvement in glycemic control.